Lifestyle factors and serum androgens among 636 middle aged men from seven countries in the European Prospective Investigation into Cancer and Nutrition (EPIC). - Suzuki, R; Allen, N; Appleby, P; Key, T; Dossus, L; Tjønneland, A; Føns Johnsen, N; Overvad, K; Sacerdote, C; Palli, D; Krogh, V; Tumino, R; et al. (2009)
OBJECTIVE: To evaluate the association between lifestyle and dietary factors and serum concentrations of androgens in middle-aged healthy men. METHODS: We conducted a cross-sectional analysis of the association of lifestyle factors with circulating concentrations of androstenedione (A-dione), 3-alpha-androstanediol glucuronide (A-diol-g), testosterone (T), SHBG (sex hormone-binding globulin), and free testosterone (FT) among 636 men in the European Prospective Investigation into Cancer and Nutrition. RESULTS: Compared with the youngest age group (40-49 years), the oldest (70-79 years) had a higher mean concentration of SHBG (by 44%) and lower mean concentrations of A-diol-g (by 29%) FT (19%). Men in the highest BMI group (> or =29.83 kg/m(2)) had a higher mean A-diol-g concentration (by 38%) and lower mean concentration of T (by 20%) SHBG (29%) compared with the lowest (<24.16 kg/m(2)). Current smokers had higher mean concentrations of T (by 13%), SHBG (14%), and A-dione (15%) compared with never smokers. Physical activity and dietary factors were not associated with androgen concentrations, although men in the highest fifth of alcohol intake had higher mean concentrations of A-dione (by 9%), FT (11%) compared with the lowest. CONCLUSION: Our results suggest that age, body weight, smoking, and alcohol intake are associated with circulating androgen concentrations in men.